تقويم الكتاب الأول لتعليم اللغة العربية بمعهد تحفيظ دار القرآن بماليزيا /bcإعداد، محمد شهر النظام بن عبد الحليف - Muhammad Shahrul Nizam bin Abdul Haliff (Kulliyah Ma'arif al-Why wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
The study aims at assessing the first book of the teaching Arabic series at the Darul Quran Tahfiz Centre in Malaysia with the purpose of looking into the contribution of learning Arabic to the tahfiz program.The researcher is of the opinion that the contents of this book was not designed to help the students improve their memorization of the verses. This is arrived at through theoretical and analytical methods used in assessing the book and looking into the general principles and criteria to designing and preparing good Arabic text book for non native speakers.The analysis standards for evaluating Arabic textbooks as described by Rushdi Tu'aimah is used and the Quranic verses in the content of the book are studied. It is hoped that this study will shed the light on the intrinsic relation between the Quran and Arabic while pointing out to the significance of the compilations on the Quranic exegesis in strengthening the Arabic of those students and developing their skills in constructing correct Arabic sentences and ultimately helping them to gain deeper understanding of the Quranic verses.